1991
DOI: 10.1037/h0079244
|View full text |Cite
|
Sign up to set email alerts
|

Learning disabilities as a childhood manifestation of severe psychopathology.

Abstract: The severity and nature of psychopathology in a group of learning disabled children was investigated. Compared to children in a normal control group, those in the learning disabled group manifested a significant degree of emotional maladjustment. They also exhibited disturbances in areas of ego functioning generally thought to be impaired in those with borderline personality organization. No linear relationship was found between severity of pathology and degree of underachievement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Among several psychopathology indexes, we highlight Opposition/Immaturity (with explanatory power for Sentences Comprehension), Aggression (with explanatory power for Sentences and Texts Comprehension), Anxiety (with explanatory power for Pseudowords Reading and Sentences Comprehension), Social Problems (with explanatory power for Sentences Comprehension), Obsessive/Schizoid (with explanatory power for Sentences Comprehension) and Depression (with explanatory power for Listening), which seem to be congruent with Knivsberg and Andreassen (2008), Sundheim and Voeller (2004), Salyer et al (1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among several psychopathology indexes, we highlight Opposition/Immaturity (with explanatory power for Sentences Comprehension), Aggression (with explanatory power for Sentences and Texts Comprehension), Anxiety (with explanatory power for Pseudowords Reading and Sentences Comprehension), Social Problems (with explanatory power for Sentences Comprehension), Obsessive/Schizoid (with explanatory power for Sentences Comprehension) and Depression (with explanatory power for Listening), which seem to be congruent with Knivsberg and Andreassen (2008), Sundheim and Voeller (2004), Salyer et al (1991).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we couldn't find previous studies about the particular effect of PS in RP. Salyer et al (1991) recognize that, when associated with learning disabilities or cognitive factors, psychological factors are easily seen as secondary and due to frustration or to manifestation of the dysfunction. However, according to Green (1989), the diversity and complexity of learning disabilities requires a multidimensional analysis that should consider, at least, individual differences (genetic, psychophysiological, cognitive, emotional, and behavioural), social network (family, relationship with peers, parental working context) and socioeconomic/cultural/political context.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, students in these categories are at risk of developing additional social and emotional adjustment problems that fall outside the defining characteristics of specific disability classifications (Morrison & Cosden, 1997). For example, although students with learning disabilities (LD) are identified by most school districts because of discrepancies between cognitive functioning and achievement, many of these students also develop emotional problems (Huntington & Bender, 1993;Salyer, Holmstrom, & Noshpitz, 1991), behavior problems (Vaughn, Zaragoza, Hogan, & Walker, 1993), and delinquency (Fink, 1990;Werner, 1993). Students identified with emotional disturbance (ED) often have achievement patterns similar to those found among students with LD (Wagner, 1995); and students with mild-mental retardation (MMR) are at risk of developing depression, as well as other emotional and behavior problems (Manikam, Matson, Coe, & Hillman, 1995;Reynolds & Miller, 1985).…”
Section: Pennsylvania State University University Parkmentioning
confidence: 99%
“…Past research with other ethnic youth samples has found a relationship between emotional problems and trouble at school (Salyer & Holmstrom, 1991;Weinberg et al, 1989). Cambodian American students also appear to be fitting into this pattern, as their tendency to withdraw more from classroom activities has been attributed to emotional factors, which may stem from the mental and physical hardships endured by the entire Cambodian community prior to immigration (Kinzie & Sack, 2002;Nguy, 2000).…”
Section: Journal Of Southeast Asian American Education and Advancementmentioning
confidence: 99%